Ideomotor representations in the training of qualified fencers-sabre fighters - Ryzhkova, L.G.; Zheng , Wenqiang (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify and explain the need to apply the method of complicating ideomotor representations in training highly skilled sabre fencers. Methods and structure of the study. An analysis of 42 scientific and methodological sources for 2000-2024 from the LIBRARY.ru, Scopus and PubMed databases was conducted, including works by Russian fencing specialists and studies by foreign authors. Content analysis, comparative analysis and theoretical modelling methods were used. Results and conclusions. It has been established that ideomotor training statistically significantly improves the technical and tactical reliability, anticipation, and mental self-regulation of sabre fencers. A model of ideomotor training has been developed that integrates the Russian concept of special methods for technical and tactical improvement (preliminary modelling of given situations, serial combat, complication of ideomotor representations when choosing actions with anticipation of distance characteristics of weapon interactions) and the principles of functional equivalence of the PETTLEP model. The complication of ideomotor representations ensures the development of cognitive flexibility, operational thinking and creative tactical behaviour of sabre fencers through four interrelated methods: a) preliminary modelling of the probable sequence of actions in a single bout; b) modelling a probabilistic sequence of actions through an ‘if-then’ system; c) independent choice and verbal commitment of the athlete to take action; d) anticipating the distance and momentary characteristics of weapon interactions.